Digvijaya Adi Sankaracharya dan Relevansinya bagi Peningkatan Pemahaman Filsafat Hindu - Yunairi, Dewi (PANGKAJA: JURNAL AGAMA HINDU, 2019)
The first person who systematically described the philosophy of Advaita was Gaudapada, who was the Parama Teacher (the teacher of teacher) of Adi Sankaracharya. Govinda the teacher from Adi Sankaracharya is a student of Gaudapada. Adi Sankaracharya was a philosopher who was able to defend and spread the philosophy of Advaita Vedanta. Digvijaya Adi Sankaracharya is a reference to understanr the Philosophy of Advaita Vedanta. His persistence in maintaining and spreading the truth of philosophy Advaita Vedanta made all his followers able to let go their thirst for knowledge and truth. The philosophy of Advaita Vedanta taught by Adi SankaracharyaÂ  is rigid and absolute. The teachings of Adi Sankaracharya in the sloka â€œBrahma Satyam Jagan Mithya, Jivo Brahmaiva Na Aparahâ€, which means that Brahman (absolute) is real, the world is not real and Jiva or personal spirit is not different from Brahman. The philosophy of Adi Sankaracharya will be a reference for people whose tendencies to know Hindu philosophy. This teaching becomes relevant in society to develop knowledge. Adi Sankaracharya comes with his philosophy to provide knowledge to anyone who is thirsty for knowledge and who has become bored with life in the world that is truly virtual. So that the teachings of Adi Sankaracharya can make it easier for Hindus to understand the teachings of Hindu Philosophy through the knowledge they have of the Philosophy of Advaita Vedanta.